Indus basin of Pakistan: Impacts of climate risks on water and agriculture - Yang, Yi-Chen; Yu, Winston; Savitsky, Andre; Alford, Donald; Brown, Casey; Wescoat, James; Debowicz, Dario; Robinson, Sherman (World Bank, 2013)
This study, Indus basin of Pakistan: the impacts of climate risks on water and agriculture was undertaken at a pivotal time in the region. The weak summer monsoon in 2009 created drought conditions throughout the country. This followed an already tenuous situation for many rural households faced with high fuel and fertilizer costs and the impacts of rising global food prices. Then catastrophic monsoon flooding in 2010 affected over 20 million people, devastating their housing, infrastructure, and crops. Damages from this single flood event were estimated at US dollar 10 billion, half of which were losses in the agriculture sector. Notwithstanding the debate as to whether these observed extremes are evidence of climate change, an investigation is needed regarding the extent to which the country is resilient to these shocks. It is thus timely, if not critical, to focus on climate risks for water, agriculture, and food security in the Indus basin of Pakistan.